Antiretroviral drugs efavirenz, dolutegravir and bictegravir dysregulate blood-brain barrier integrity and function - Huang, Chang; Hoque, Tozammel; Bendayan, Reina (Frontiers in Pharmacology, 2023)
The implementation of combined antiretroviral therapy (cART) significantly reduces the mortality associated with human immunodeficiency virus (HIV) infection. However, complications such as HIV-associated neurocognitive disorders (HAND) remain a major health concern. We hypothesized that the toxicity of antiretroviral drugs (ARVs) may contribute to the pathogenesis of HAND in addition to cerebral viral infection. To address this question, we evaluated the impact of HIV integrase strand transfer inhibitors (dolutegravir and bictegravir), and a non-nucleoside reverse transcriptase inhibitor (efavirenz) on the integrity and permeability of various human and mouse blood-brain barrier (BBB) models, in vitro, ex vivo and in vivo. We observed a significant downregulation of tight junction proteins (TJP1/Tjp1, OCLN/Ocln and CLDN5/Cldn5), upregulation of proinflammatory cytokines (IL6/Il6, IL8/Il8, IL1b/Il1b) and NOS2/Nos2, and alteration of membrane-associated transporters (ABCB1/ABCB1a, ABCG2/Abcg2 and SLC2A1/Slc2a1) mRNA expression, in vitro, in human (hCMEC/D3) and primary cultures of mouse microvascular endothelial cells, and ex vivo in isolated mouse brain capillaries treated with efavirenz, dolutegravir, and/or bictegravir. We also observed a significant increase in BBB permeability in vivo following treatment with the selected ARVs in mice applying NaF permeability assay. Taken together, these results suggest that recommended integrase strand transfer inhibitors such as dolutegravir may exacerbate HIV-associated cerebrovascular pathology, which may contribute to the associated short-term neuropsychiatric side effects and the high incidence of mild forms of HAND reported in the clinical setting.